Penerapan Model Pembelajaran Interaktif Tipe Course Review Horay Pada Pembelajaran Biologi Di Sma Negeri 1 Labuapi - Wijayanti, Tri Sari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to improve student’s learning outcomes in kingdom protista materials by using an interactive learning model on course review horay type. This study is Classroom Action Research (CAR) which is conducted in two cycles, each cycle consists of two meetings and four stages (planning, action, observation, and reflection). The subject of this study is students of class X which is consisting 36 students of SMAN 1 labuapi West Lombok. Data collection use observation, test, and documentation. Data analysis use qualitative and quantitative analysis. The results shows that student’s activities cycle I is 51.72% in first meeting and 62.07% in second meeting. Cycle II is 68.9% in first meeting and 77.59% in second meeting with a very good category. Teacher’s activity cycle I is 56% in first meeting and 72% in second meeting. Cycle II is 75% in first meeting and 81.25% in second meeting. The classical learning outcomes of students is 68.90% in first cycle with good category and 89.65% in second cycle with very good category. It concluded that using an interactive learning model of course review horay type can improve biology learning outcomes of class X students of SMAN 1 Labuapi West Lombok.